TRANSFORMATIONAL AND TRANSACTIONAL LEADERSHIP STYLES TOWARDS ORGANIZATIONAL COMMITMENT IN THE HOTEL INDUSTRY - Toh Pei Sung; Liew Wan Joo; Iklima Husna Abdul Rahim; Stephen Sondoh, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
In the hotel industry, high service quality has become a concern to the hotel service providers as a means for gaining a competitive advantage since hotels provide similar services. Apart from that, hotels need to have committed staff towards improving the quality of service. In this context, the organizational commitment of operational employees is necessary for providing better services for the guest. The leadership styles in the hotel industry can provide different motivators that leads to organizational commitment. Therefore, the purpose of the study is to examine the perception of the relationship between leadership styles (transformational and transactional) and organizational commitment. The quantitative approach was applied in this study by using questionnaires through a survey. The data analysis was tested by using the SmartPLS 3.0 software. The results suggested that transactional leadership style and transformational leadership styles have a positive relationship with organizational commitment.